"Porta do Céu": o processo de cristianização da Freguesia de Nossa Senhora da Apresentação (1681-1714) - Costa, Renata Assunção da (2015)
This study aims to analyze the process of Christianization space in the different areas of the Parish of Our lady of Presentation between 1681 and 1714. To accomplish this goal, the main primary sources researched was the parish records of baptism. Thus, areas of the parish were designed based on two fundamental concepts: Christianization of the locations (and souls), based on the study of Claudia Damasceno, who worked with the notion of ecclesiastical circumscription, adapted for the case of Parish of Our lady of Presentation, and the concept of local experimentation, by Yi-Fu Tuan. Christianization the areas was the process of transformation of spatial logic, found previously by the Portuguese, by overlapping the ecclesiastical logic over Indigenous perception, through buildings construction, to initiate people to Catholicism. The experiment, in turn, would be made by the local residents studied and by religious themselves, making these areas, in places, in the sense of achieving new local meanings. It was verified, therefore, that Parish of Our lady of Presentation had at least three distinct places, the City of Natal, the villages around and the parish missions. Then, the focus of this thesis is to analyze how settlers used these different places as religious meanings.